Stereo composite polylactic acid / silicon dioxide composite material and preparation method thereof
By preparing stereocomposite polylactic acid/silica composite materials, using temperature gradient guided directional crystallization and freeze-drying, the problem of degradation of polymer-based radiation refrigeration materials is solved, and efficient radiation refrigeration performance and structural strength are achieved.
Patent Information
- Application Number
- CN202411771929.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-25
AI Technical Summary
The stability of existing polymer-based radiation refrigeration materials decreases after long-term exposure to ultraviolet rays, resulting in a significant reduction in cooling performance.
By using the preparation method of stereocomposite polylactic acid/silica composite, by mixing levoposite polylactic acid and dextroposite polylactic acid with nanosilica in a hexafluoroisopropanol solution, heating and stirring, the solution is directed to crystallize with a temperature gradient and freeze-dried to form a composite material with radiation refrigeration properties.
The thermal stability and mechanical properties of the material are improved, the radiation refrigeration performance is enhanced, the reflectivity and emissivity of the material are improved, and the cooling effect is significant.
Smart Images

Figure CN119505501A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of radiation refrigeration material preparation, and relates to a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance and a preparation method thereof. Background Art
[0002] In many fields such as construction and automobiles, thermal insulation materials are often used to slow down the transfer of heat, thereby achieving a cooling effect. These materials cannot prevent the transfer of heat, and the cooling effect is limited. In addition, most traditional thermal insulation materials are not biodegradable, which is not conducive to green development. Therefore, it is particularly urgent to develop new refrigeration materials that are both energy-efficient and environmentally friendly. This new refrigeration material will help reduce the refrigeration system's dependence on electricity, thereby reducing carbon emissions and promoting sustainable development.
[0003] Radiative cooling technology is an emerging refrigeration method. Radiative cooling is a passive refrigeration technology that does not consume energy. It reduces the surface temperature of ground objects with zero energy consumption by transferring excess heat to the universe (the cosmic background temperature is 3K). Radiative cooling mainly radiates mid-infrared waves with a wavelength of 7 to 14 μm to the outside world, while reflecting visible light and near-infrared waves with a wavelength of 400nm to 2 μm, thereby achieving cooling. This technology has the advantages of low energy consumption and high efficiency. Currently, the materials used for radiative cooling are mainly divided into polymer-based materials, inorganic materials and polymer / inorganic composite materials.
[0004] Polymer-based radiative cooling materials have attracted widespread attention due to their high infrared emissivity and easy preparation of highly reflective structures. For example, porous polymer films prepared by techniques such as electrospinning can achieve an ambient cooling of about 6°C under direct sunlight. In addition, doping polymers such as polyethylene oxide with nanofibers can significantly improve their mechanical and light stability. However, most polymer-based radiative cooling materials face environmental stability issues. Long-term exposure to ultraviolet rays will cause yellowing reactions, resulting in increased visible light absorption and significantly reduced cooling performance, such as polyurethane-based materials. In addition, their mechanical properties are affected by the porosity required for daytime radiative cooling. Although the porous structure can enhance sunlight reflection, it will sacrifice the rigidity of the material, resulting in a decrease in mechanical stability. Summary of the invention
[0005] The purpose of the present invention is to solve the problem in the prior art that the stability of polymer-based radiation refrigeration materials is low, resulting in significantly reduced cooling performance, and to provide a stereocomposite polylactic acid / silicon dioxide composite material and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a stereocomposite polylactic acid / silicon dioxide composite material, comprising:
[0008] preparing a stereocomposite polylactic acid solution and a nano-silicon dioxide dispersion solution;
[0009] The stereocomplex polylactic acid solution and the nano-silicon dioxide dispersion are mixed, and heated and stirred to obtain a mixed solution;
[0010] The mixed solution is poured into a mold, and the two ends of the mold are placed in different ambient temperatures to form a temperature gradient, and the mixed solution is guided to crystallize along the temperature gradient until it is completely frozen;
[0011] The mold is freeze-dried to obtain a stereocomposite polylactic acid / silicon dioxide composite material.
[0012] Preferably, the steps of preparing the stereocomposite polylactic acid solution are as follows:
[0013] The left-handed polylactic acid and the right-handed polylactic acid are dissolved in a hexafluoroisopropanol solution and stirred at room temperature until they are completely dissolved to prepare a stereocomposite polylactic acid solution.
[0014] Preferably, the molar ratio of L-polylactic acid, D-polylactic acid and hexafluoroisopropanol solution is 0.0056-0.0133 mol: 0.0056-0.0133 mol: 0.067 mol-0.333 mol.
[0015] Preferably, the weight average molecular weight ratio of L-polylactic acid to D-polylactic acid is 1:1.
[0016] Preferably, the steps of preparing the nano-silicon dioxide dispersion solution are as follows:
[0017] The nano-silicon dioxide is dispersed in a hexafluoroisopropanol solution and ultrasonicated until uniformly dispersed to prepare a nano-silicon dioxide dispersion solution.
[0018] Preferably, the particle size of the nano-silicon dioxide is 20 nm to 100 nm, and the ultrasonic time is 20 min to 60 min.
[0019] Preferably, the molar ratio of nano-silicon dioxide to hexafluoroisopropanol solution is 0.0003 mol to 0.0017 mol: 0.028 mol to 0.142 mol.
[0020] Preferably, the heating and stirring temperature is 293.15K to 333.15K, and the heating and stirring time is 5min to 20min.
[0021] Preferably, the mold is a low-temperature resistant mold with energy transfer performance, the freeze-drying time is 24h to 48h, and the freeze-drying temperature is 193.15K to 233.15K.
[0022] A stereocomposite polylactic acid / silicon dioxide composite material is prepared by a method for preparing a stereocomposite polylactic acid / silicon dioxide composite material.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The invention discloses a method for preparing a stereocomposite polylactic acid / silicon dioxide composite material. Different from traditional thermal insulation materials, the stereocomposite polylactic acid / silicon dioxide composite material has a radiation cooling function, can reflect visible light and near-infrared waves, radiate mid-infrared waves, and can better control the transfer of heat. The polylactic acid used in the invention is mainly derived from renewable resources, such as plants such as corn and cassava. In the natural environment, polylactic acid can be completely degraded into carbon dioxide and water by the action of microorganisms, has good biodegradability, and is environmentally friendly. As a green and low-carbon material, polylactic acid helps to reduce carbon emissions, which is in line with the global trend of carbon reduction and environmental protection. By mixing left-handed polylactic acid and right-handed polylactic acid to form a stereocomposite polylactic acid, the radiation cooling performance can be improved and the structural strength of the material can be enhanced. Compared with ordinary polylactic acid materials, the stereocomposite polylactic acid material has good thermal stability and mechanical properties. Inorganic material nano-silica is widely used to improve the radiation cooling performance and mechanical properties of materials due to its unique optical and physical properties. By combining silica nanoparticles with stereocomposite polylactic acid, a temperature difference is created to guide the solvent to undergo low-temperature freezing and directional crystallization and freeze-drying, thereby forming a stereocomposite polylactic acid / silicon dioxide composite material with an ordered structure. The successfully constructed ordered physical structure can not only improve the mechanical properties of the material, but also improve the radiation cooling characteristics of the material.
[0025] Furthermore, by controlling the weight average molecular weight of L-polylactic acid and D-polylactic acid, the production of stereocomplex polylactic acid can be effectively increased, thereby improving the radiation cooling performance and structural strength of the material.
[0026] Furthermore, by controlling the concentration of left-handed polylactic acid and right-handed polylactic acid in the solution, the pore size of the pores in the ordered physical structure can be regulated, thereby improving the performance of radiative cooling.
[0027] Furthermore, the performance of radiative cooling can be improved by controlling the particle size of nano-silica.
[0028] Furthermore, the performance of radiative cooling can be improved by controlling the mass fraction of nano-silicon dioxide.
[0029] Furthermore, by controlling the heating time of the oil bath, the production of stereocomplex polylactic acid can be effectively increased, thereby improving the radiation cooling performance and structural strength of the material.
[0030] Furthermore, by controlling the heating temperature of the oil bath, the production of stereocomplex polylactic acid can be effectively increased, thereby improving the radiation cooling performance and structural strength of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 The present invention is a flow chart of preparing a stereocomposite polylactic acid / silicon dioxide radiation refrigeration composite material.
[0033] Figure 2 It is an infrared spectrum of the stereocomposite polylactic acid / silicon dioxide radiation refrigeration composite material prepared by the present invention.
[0034] Figure 3 This is a physical picture of the stereocomposite polylactic acid / silicon dioxide radiation refrigeration composite material prepared by the present invention.
[0035] Figure 4 It is a SEM picture of the stereocomposite polylactic acid / silicon dioxide radiation refrigeration composite material prepared by the present invention.
[0036] Figure 5 This is the cooling condition of the stereocomposite polylactic acid / silicon dioxide radiation refrigeration composite material prepared by the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0038] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0040] In the description of the embodiments of the present invention, it should be noted that if the terms "upper", "lower", "horizontal", "inner", etc. indicate an orientation or positional relationship based on the orientation or positional relationship shown in the drawings, or the orientation or positional relationship in which the product of the invention is usually placed when in use, it is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.
[0041] In addition, if the term "horizontal" appears, it does not mean that the component must be absolutely horizontal, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", which does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0042] In the description of the embodiments of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0043] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0044] The present invention provides a method for preparing a stereocomposite polylactic acid / silicon dioxide composite material with radiative cooling performance, comprising the following steps:
[0045] Step 1, preparing a stereocomposite polylactic acid solution and a nano-silicon dioxide dispersion solution;
[0046] The steps for preparing the stereocomposite polylactic acid solution are as follows:
[0047] The left-handed polylactic acid and the right-handed polylactic acid are dissolved in a hexafluoroisopropanol solution and stirred at room temperature until they are completely dissolved to prepare a stereocomposite polylactic acid solution.
[0048] The molar ratio of L-polylactic acid, D-polylactic acid and hexafluoroisopropanol solution is 0.0056-0.0133 mol: 0.0056-0.0133 mol: 0.067 mol-0.333 mol.
[0049] The weight average molecular weight ratio of L-polylactic acid to D-polylactic acid is 1:1.
[0050] The steps for preparing nano-silicon dioxide dispersion solution are as follows:
[0051] The nano-silicon dioxide is dispersed in a hexafluoroisopropanol solution and ultrasonicated until uniformly dispersed to prepare a nano-silicon dioxide dispersion solution.
[0052] The particle size of the nano-silicon dioxide is 20nm-100nm, and the ultrasonic time is 20min-60min.
[0053] The molar ratio of nano silicon dioxide to hexafluoroisopropanol solution is 0.0003 mol to 0.0017 mol: 0.028 mol to 0.142 mol.
[0054] Step 2, mixing the stereocomposite polylactic acid solution and the nano-silicon dioxide dispersion, heating and stirring to obtain a mixed solution;
[0055] The heating and stirring temperature is 293.15K to 333.15K, and the heating and stirring time is 5min to 20min.
[0056] Step 3: pour the mixed solution into a mold, place the two ends of the mold at different ambient temperatures to form a temperature gradient, and guide the mixed solution to crystallize along the temperature gradient until it is completely frozen; wherein, liquid nitrogen is used at one end of the mold and room temperature is used at the other end.
[0057] Step 4: freeze-drying the mold to obtain a stereocomposite polylactic acid / silicon dioxide composite material.
[0058] The mold is a low-temperature resistant mold with energy transfer performance. The freeze-drying time is 24h to 48h, and the freeze-drying temperature is 193.15K to 233.15K.
[0059] The weight average molecular weight (Mw) of the L-polylactic acid and the D-polylactic acid is 30,000 to 60,000 g / mol.
[0060] The following is a detailed description of this method:
[0061] Example 1
[0062] Take 0.0056mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 60000g / mol and 0.0056mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 60000g / mol and dissolve them in 0.067mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0003mol of 100nm nano-silicon dioxide and evenly disperse it in 0.028mol of hexafluoroisopropanol, ultrasonicate for 60min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After mixing the polylactic acid solution with the nano-silicon dioxide dispersion, heat and stir it in an oil bath at 293.15K for 20min. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (233.15K) for freeze drying for 24h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0063] Example 2
[0064] Take 0.0067mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 30000g / mol and 0.0067mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 30000g / mol and dissolve them in 0.067mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0007mol of 30nm nano-silicon dioxide and evenly disperse it in 0.028mol of hexafluoroisopropanol, ultrasonicate for 30min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After mixing the polylactic acid solution with the nano-silicon dioxide dispersion, heat and stir for 5min in an oil bath at 313.15K. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (223.15K) and freeze-dry for 36h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0065] Example 3
[0066] Take 0.0078mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 40000g / mol and 0.0078mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 40000g / mol and dissolve them in 0.134mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0005mol of 40nm nano-silicon dioxide and evenly disperse it in 0.057mol of hexafluoroisopropanol, ultrasonicate for 40min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After mixing the polylactic acid solution with the nano-silicon dioxide dispersion, heat and stir for 20min in an oil bath at 303.15K. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (193.15K) and freeze-dry for 24h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0067] Example 4
[0068] Take 0.0090mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 45000g / mol and 0.0090mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 45000g / mol and dissolve them in 0.167mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0010mol of 90nm nano-silicon dioxide and evenly disperse it in 0.071mol of hexafluoroisopropanol, ultrasonicate for 50min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After the polylactic acid solution and the nano-silicon dioxide dispersion are mixed, heat and stir for 5min in an oil bath at 323.15K. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (203.15K) and freeze-dry for 48h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0069] Example 5
[0070] Take 0.0100mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 55000g / mol and 0.0100mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 55000g / mol and dissolve them in 0.200mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0013mol of 70nm nano-silicon dioxide and evenly disperse it in 0.086mol of hexafluoroisopropanol, ultrasonicate for 60min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After mixing the polylactic acid solution with the nano-silicon dioxide dispersion, heat and stir for 15min in an oil bath at 298.15K. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (213.15K) and freeze-dry for 24h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0071] Example 6
[0072] Take 0.0111mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 50000g / mol and 0.0111mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 50000g / mol and dissolve them in 0.200mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0008mol of 50nm nano-silicon dioxide and evenly disperse it in 0.086mol of hexafluoroisopropanol, ultrasonicate for 25min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After mixing the polylactic acid solution with the nano-silicon dioxide dispersion, heat and stir it in an oil bath at 293.15K for 20min. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (193.15K) and freeze-dry it for 24h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0073] Example 7
[0074] Take 0.0122mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 35000g / mol and 0.0122mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 35000g / mol and dissolve them in 0.267mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0007mol of 60nm nano-silicon dioxide and evenly disperse it in 0.114mol of hexafluoroisopropanol, ultrasonicate for 40min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After mixing the polylactic acid solution with the nano-silicon dioxide dispersion, heat and stir for 10min in an oil bath at 328.15K. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (233.15K) and freeze-dry for 36h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0075] Example 8
[0076] Take 0.0056mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 50000g / mol and 0.0056mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 50000g / mol and dissolve them in 0.067mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0010mol of 30nm nano-silicon dioxide and evenly disperse it in 0.028mol of hexafluoroisopropanol, ultrasonicate for 30min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After mixing the polylactic acid solution with the nano-silicon dioxide dispersion, heat and stir for 10min in an oil bath at 333.15K. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (213.15K) and freeze-dry for 48h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0077] Example 9
[0078] Take 0.0100mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 35000g / mol and 0.0100mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 35000g / mol and dissolve them in 0.300mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0015mol of 80nm nano-silicon dioxide and evenly disperse it in 0.128mol of hexafluoroisopropanol, ultrasonicate for 60min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After mixing the polylactic acid solution with the nano-silicon dioxide dispersion, heat and stir for 15min in an oil bath at 313.15K. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (213.15K) and freeze-dry for 36h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0079] Example 10
[0080] Take 0.0133mol of left-handed polylactic acid with a weight average molecular weight (Mw) of 30000g / mol and 0.0133mol of right-handed polylactic acid with a weight average molecular weight (Mw) of 30000g / mol and dissolve them in 0.333mol of hexafluoroisopropanol, stir until completely dissolved, and obtain a polylactic acid solution. Take 0.0017mol of 20nm nano-silicon dioxide and evenly disperse it in 0.142mol of hexafluoroisopropanol, ultrasonicate for 20min until evenly dispersed, and obtain a nano-silicon dioxide dispersion. After mixing the polylactic acid solution with the nano-silicon dioxide dispersion, heat and stir for 5min in an oil bath at 333.15K. Pour the mixed solution into a mold, and use low temperature to guide the solution to crystallize in an oriented manner until it is completely frozen. Put the mold into a freeze dryer (193.15K) and freeze-dry for 48h to obtain a stereocomposite polylactic acid / silicon dioxide composite material with radiation refrigeration performance.
[0081] Take Example 1 of the present invention as experimental group 1, Example 2 as experimental group 2, Example 3 as experimental group 3, Example 4 as experimental group 4, Example 5 as experimental group 5, Example 6 as experimental group 6, Example 7 as experimental group 7, Example 8 as experimental group 8, Example 9 as experimental group 9, and Example 10 as experimental group 10.
[0082] The materials prepared from the above 10 groups of experiments were analyzed and the following results were obtained:
[0083] An infrared thermal imager was used to measure the cooling of the surface temperature of 10 groups of experimentally prepared materials relative to the background temperature under full-spectrum light irradiation. Different material samples were characterized by Fourier infrared spectroscopy and scanning electron microscopy. The chemical structure and composition of the materials, as well as the physical structure, were analyzed. Among them, Example 8 had the best effect, with the highest reflectivity and emissivity of the material, and the best cooling effect.
[0084] Figure 2 This is the infrared spectrum of the stereocomposite polylactic acid / silicon dioxide radiation cooling composite material. Figure 2 Medium, 2995cm -1 and 2945cm -1 The stretching vibration absorption peak of polylactic acid CH is 1757 cm -1 It is the characteristic absorption peak of C=O in polylactic acid group, 1460cm -1 and 1383cm -1 The bending vibration absorption peak of polylactic acid CH is 1180cm -1 is the polylactic acid CO stretching vibration absorption peak, 1079cm -1 It is the polylactic acid COC stretching vibration absorption peak, 908cm -1 It is the characteristic absorption peak of stereocomposite polylactic acid SC-PLA, 865cm -1 and 754cm -1 The peaks at 1100 cm-1 indicate that there are both crystalline and non-crystalline regions in PLA. -1 The antisymmetric stretching vibration absorption peak of Si-O-Si of silicon dioxide is 810 cm -1 is the symmetrical stretching vibration absorption peak of silicon dioxide Si-O-Si, 470 cm -1 It is the characteristic absorption peak of silicon dioxide. The stereocomposite polylactic acid / silicon dioxide curve has a corresponding characteristic peak appearing at the corresponding position, proving the successful preparation of the stereocomposite polylactic acid / silicon dioxide material.
[0085] like Figure 3 This is a physical picture of the stereocomposite polylactic acid / silicon dioxide radiation refrigeration composite material.
[0086] like Figure 4 This is the SEM image of the material at 50 μm size. Figure 4 It can be seen that the material has a certain ordered physical structure, which helps to improve the radiation cooling performance of the material.
[0087] like Figure 5 To investigate the cooling of the stereocomposite polylactic acid / silicon dioxide radiative cooling composite material, the material was placed 20 cm away from a full-spectrum lamp and the temperature changes of the material were recorded. Figure 5 (a) is the temperature change of the material. Figure 5 (b) shows the temperature reduction of the material relative to the background glass plate. The cooling effect can reach 8 to 9°C.
[0088] Table 1 Average reflectivity of stereocomposite polylactic acid / silicon dioxide radiative cooling composite materials
[0089]
[0090] Table 2 Average emissivity of stereocomposite polylactic acid / silicon dioxide radiative cooling composite materials
[0091]
[0092] It can be seen from Table 1 that the average reflectivity of the material in the key wavelength range can reach more than 92%, and it can be seen from Table 2 that the average emissivity of the material in the key wavelength range can reach more than 86%. The stereocomposite polylactic acid / silicon dioxide radiation cooling composite material has good radiation cooling performance.
[0093] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a stereocomposite polylactic acid / silicon dioxide composite material, characterized in that: include: preparing stereocomposite polylactic acid solution and nano-silicon dioxide dispersion solution; The stereocomplex polylactic acid solution and the nano-silicon dioxide dispersion are mixed, and heated and stirred to obtain a mixed solution; The mixed solution is poured into a mold, and the two ends of the mold are placed in different ambient temperatures to form a temperature gradient, and the mixed solution is guided to crystallize along the temperature gradient until it is completely frozen; The mold is freeze-dried to obtain a stereocomposite polylactic acid / silicon dioxide composite material.
2. The method for preparing the stereocomplex polylactic acid / silicon dioxide composite material according to claim 1, characterized in that: The steps for preparing the stereocomposite polylactic acid solution are as follows: The left-handed polylactic acid and the right-handed polylactic acid are dissolved in a hexafluoroisopropanol solution and stirred at room temperature until they are completely dissolved to prepare a stereocomposite polylactic acid solution.
3. The method for preparing the stereocomplex polylactic acid / silicon dioxide composite material according to claim 2, characterized in that: The molar ratio of L-polylactic acid, D-polylactic acid and hexafluoroisopropanol solution is 0.0056-0.0133 mol: 0.0056-0.0133 mol: 0.067 mol-0.333 mol.
4. The method for preparing the stereocomplex polylactic acid / silicon dioxide composite material according to claim 2, characterized in that: The weight average molecular weight ratio of L-polylactic acid to D-polylactic acid is 1:
1.
5. The method for preparing the stereocomplex polylactic acid / silicon dioxide composite material according to claim 1, characterized in that: The steps for preparing nano-silicon dioxide dispersion solution are as follows: The nano-silicon dioxide is dispersed in a hexafluoroisopropanol solution and ultrasonicated until uniformly dispersed to prepare a nano-silicon dioxide dispersion solution.
6. The method for preparing the stereocomplex polylactic acid / silicon dioxide composite material according to claim 5, characterized in that: The particle size of the nano-silicon dioxide is 20nm-100nm, and the ultrasonic time is 20min-60min.
7. The method for preparing the stereocomplex polylactic acid / silicon dioxide composite material according to claim 5, characterized in that: The molar ratio of nano silicon dioxide to hexafluoroisopropanol solution is 0.0003 mol to 0.0017 mol: 0.028 mol to 0.142 mol.
8. The method for preparing the stereocomplex polylactic acid / silicon dioxide composite material according to claim 1, characterized in that: The heating and stirring temperature is 293.15K to 333.15K, and the heating and stirring time is 5min to 20min.
9. The method for preparing the stereocomplex polylactic acid / silicon dioxide composite material according to claim 1, characterized in that: The mold is a low-temperature resistant mold with energy transfer performance. The freeze-drying time is 24h to 48h, and the freeze-drying temperature is 193.15K to 233.15K.
10. A stereocomplex polylactic acid / silicon dioxide composite material, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing ordered-structure porous polymer material based on directional crystallization technology
CN102850574A
Heat-resistant and degradable radiation refrigeration film as well as preparation method and application thereof
CN111334012A
Degradable high-hydrophobicity aerogel porous material and preparation method thereof
CN114085418A
Porous radiation refrigeration film and preparation method thereof
CN116515219A
Preparation method of composite porous material with passive radiation refrigeration function
CN117106225A